Bis(2-[alpha-hydroxyethyl]benzimidazolato)copper(II) anchored onto chloromethylated polystyrene for the biomimetic oxidative coupling of 2-aminophenol to 2-aminophenoxazine-3-one - Maurya, Mannar R.; Sikarwar, S.; Joseph, Trissa; Halligudi, Shivappa B. (Journal of Molecular Catalysis A - Chemical, 2005)
2-(alpha-Hydroxyethyl)benzimidazole (Hhebmz) has been covalently anchored to chloromethylated polystyrene cross-linked with 5% divinylbenzene. This polymer-anchored chelating resin reacts with cupric acetate in presence of Hhebmz to give polymer-anchored copper(II) complex PS-[Cu(hebmz)(2)]. Elemental analyses, FT-IR, electronic, scanning electron micrographs (SEM) and TGA-DTA pattern have been used to characterize the complex. Oxidative coupling of 2-aminophenol (OAP) to 2-aminophenoxazine-3-one (APX) catalyzed by PS-[Cu(hebmz)(2)] in presence of air at 70 degrees C in DMF gave 62% substrate conversion over a period of 8 h. Kinetics of the above reaction indicated that the rate of oxidative coupling of OAP has a first order dependence with respect to substrate, catalyst and air pressure (dissolved O-2) concentrations in the range of conditions evaluated. Based on these observations, a plausible mechanism for the above reaction has been proposed. From, the study on the effect of temperature on the rates of oxidative coupling, an activation energy 34.2 kcal/degree mole was evaluated from Arrhenius plot of -ln rate versus 1/T. Enthalpy, entropy and free energy were calculated using standard thermodynamic equations for the above reaction. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: 2-aminophenol; 2-aminophenoxazine-3-one; bis(2-[alpha-hydroxyethyl]benzimidazolato)copper(II); chloromethylated polystyrene; oxidative coupling

Bronsted acidic ionic liquids: a green, efficient and reusable catalyst system and reaction medium for fischer esterification - Joseph, Trissa; Sahoo, S.; Halligudi, Shivappa B. (Journal of Molecular Catalysis A - Chemical, 2005)
Bronsted acidic ionic liquid containing nitrogen-based organic cations 1-methylimidazole and 1-butyl-3-methylimidazolium and inorganic anions of the type BF4-, PF6- and PTSA(-) has been synthesized in good yields and used as a catalysts and reaction medium for Fischer esterification of alcohols with acids. These were characterized using FTIR and NMR spectroscopy. Ionic liquids as catalyst afforded good alcohol conversion and excellent ester selectivity. Fischer esterification of acetic acid with benzyl alcohol with different Bronsted acidic ionic liquids was carried out. Maximum substrate conversion 100 % and product selectivity 100 % was observed on using [BMIM](+)PTSAas catalyst over a period of 2 h. The ester was easily separated from the reaction mixture and the ionic liquid was reused four times after removing water. No significant loss in catalytic activity was observed on recycling. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: acids; alcohol and reaction medium; Fischer esterification; Ionic liquid